2011
DOI: 10.1111/j.1745-4549.2011.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Egg and Egg Replacers on Yellow Cake Product Quality

Abstract: Five yellow cake formulations, prepared with liquid whole egg, dry whole egg and three commercial egg replacers (soy/wheat, whey protein and fiber/gum‐based), were evaluated to determine differences in end‐product qualities influenced by the differences in ingredient compositions. The products were prepared following the same procedure and other ingredient compositions, except for the egg or egg replacer used in the formulation. The physical product characteristics and sensory properties of the end products we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 12 publications
1
19
0
2
Order By: Relevance
“…Addition of DSFS increased the viscosity from 18,700 to 44,000 Pa s; increased volume from 600 to 640 cm 3 /330 g of batter and moisture from 29.22 to 35.38% and decreased specific gravity from 1.08 to 1.03 g/cc. These results are due to soy protein and flax seed having excellent gelling, emulsifying properties and binding properties, respectively, similar to egg (Oomah, ; Ratnayake et al ). Hardness value for eggless cake was 42.51 N. Addition of DSFS significantly decreased the hardness value (42.51–38.51 N), increased the springiness value which from 6.81 to 8.81 mm and decreased the gumminess value from 12.91 to 11.51 N. Generally batters with high viscosity readings made cakes that scored high in tenderness, velvetiness, evenness of grain after baking (Matthews & Dawson, ).…”
Section: Resultsmentioning
confidence: 99%
“…Addition of DSFS increased the viscosity from 18,700 to 44,000 Pa s; increased volume from 600 to 640 cm 3 /330 g of batter and moisture from 29.22 to 35.38% and decreased specific gravity from 1.08 to 1.03 g/cc. These results are due to soy protein and flax seed having excellent gelling, emulsifying properties and binding properties, respectively, similar to egg (Oomah, ; Ratnayake et al ). Hardness value for eggless cake was 42.51 N. Addition of DSFS significantly decreased the hardness value (42.51–38.51 N), increased the springiness value which from 6.81 to 8.81 mm and decreased the gumminess value from 12.91 to 11.51 N. Generally batters with high viscosity readings made cakes that scored high in tenderness, velvetiness, evenness of grain after baking (Matthews & Dawson, ).…”
Section: Resultsmentioning
confidence: 99%
“…When just WPPC was added, the yield did not significantly change, which can be attributed to the water holding capacity of the WPPC maintaining the same moisture as the whole eggs. Previous research has shown that eggs and whey proteins can hold similar amounts of water (Ratnayake et al, 2012).…”
Section: Cakementioning
confidence: 99%
“…Ratnayake et al. () partially substituted eggs with three commercial egg replacers and reported that they affected moisture retention, texture, color, bulk density, and flavor; however, some of these changes were not distinguished in sensory evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, acquiring cost-effective and healthy sources for partial or total replacement of egg is of great importance. Egg has several functional properties including forming a part of cake structure, coloring, flavoring, binding, foaming, tenderizing, emulsifying, and improvement of nutritive value of cake (Ashwini et al, 2009;Ratnayake, Geera, & Rybak, 2012;Wilderjans, Luyts, Brijs, & Delcour, 2013). Therefore, finding an appropriate substitute for eggs is difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation